2022-RA-1293-ESGO Validation of a sustainable internationally monitored cervical cancer screening system using a visual smartphone inspection in Kinshasa. (20th October 2022) - Tendobi, Celine; Carlos, Silvia; Lozano, Maria Dolores; Auba, Maria; Caparros, Maria; Garcia-Sanz, Maria; Vara, Julio; Lopez-Picazo, Ana; Fernandez-Marques, Margarita; Reina, Gabriel; Jurado, Matias; Alcazar, Juan Luis; et al.
Abstract : Introduction/Background: To determine the sensitivity, specificity, positive and negative predictive values of a cervical cancer screening program based on visual inspection with acetic acid and Lugol´s-iodine using a smartphone in a sub-urban area of very low resources in Kinshasa. Methodology: This cross-sectional validation study was conducted at Monkole-Hospital and it included women between the ages of 25–70 after announcing a free cervical cancer screening campaign through posters placed in the region of our hospital. Questionnaires collected sociodemographic and behavioral patient characteristics. In the first consultation, we gathered liquid-based cytology samples from every woman. At that time, local health providers performed two combined visual inspection techniques (5% acetic acid and Lugol´s iodine) while a picture was performed with a smartphone. Two international specialists evaluated the results of the smartphone cervicography. When a visual inspection was considered suspicious, patients were offered immediate cryotherapy. Cytological samples were sent to the Pathology Department of the University of Navarra for cytological assessment and HPV DNA genotyping. Results: A total of 480 women participated in the study. The mean age was 44.6 years (Range 25–65). Of all patients, only 18.7% were infected with HPV (75% had high-risk genotypes). The most frequent high-risk genotype found was 16 (12.4%). The majority (88%) of women had normal cytology. After comparing combined visual inspection results with cytology, we found a sensitivity of 66.0%, a specificity of 87.6%, a positive predictive value of 40.2%, and a negative predictive value of 95.3% for any cytological lesion. The negative predictive value for high-grade lesions was 99.7%. Conclusion: Cervical cancer screening through combined-visual inspection, conducted by non-specialized personnel and monitored by experts through smartphones, shows encouraging results, ruling out high-grade cytological lesions in most cases. This combined visual inspection test is a valid and affordable method for screening programs in low-income areas.